Negotiated assessment and teacher learning: An in-depth exploration. (July 2015) - Verberg, Christel P.M.; Tigelaar, Dineke E.H.; Verloop, Nico
Abstract: Opportunities for negotiation in formative assessment may benefit teachers' professional development. Detailed analysis of nine assessment dialogues involving pairs of nursing teachers in secondary vocational education showed that the amount of negotiation was limited . Assessment dialogues provided ample opportunities for negotiation (based on expressed disagreement), but more than half of these opportunities were neglected and hence not used to negotiate learning implications. Participants found it difficult to confront a colleague. Possible reasons for this, also methodological, are discussed with a view to future training, formative assessment and research. Highlights: Opportunities for negotiation in formative assessment may benefit teacher learning. More information about the negotiation process is needed. We developed a formative assessment procedure with opportunities for negotiation. Both teachers and their peer assessors neglected many opportunities for negotiation. Participants found it difficult to confront a colleague while negotiating.